2020
DOI: 10.1002/glia.23844
|View full text |Cite
|
Sign up to set email alerts
|

Microglia influence host defense, disease, and repair following murine coronavirus infection of the central nervous system

Abstract: The present study examines functional contributions of microglia in host defense, demyelination, and remyelination following infection of susceptible mice with a neurotropic coronavirus. Treatment with PLX5622, an inhibitor of colony stimulating factor 1 receptor (CSF1R) that efficiently depletes microglia, prior to infection of the central nervous system (CNS) with the neurotropic JHM strain of mouse hepatitis virus (JHMV) resulted in increased mortality compared with control mice that correlated with impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 67 publications
(97 reference statements)
11
55
1
Order By: Relevance
“…In addition to the astroglial role in preventing CNS spreading of MHV-A59, microglia seem also to be required to control neurotropic CoV infection. A recently published article showed that depletion of microglia using PLX5622, an inhibitor of colony-stimulating factor 1 receptor (CSF1R), in animals exposed to JHM-MHV increased mortality, impaired control of viral replication, altered CD4+ and CD8+ T-cell infiltration, increased demyelination, and decreased neuro-repair ( Mangale et al., 2020 ).…”
Section: Animal Cov That Show Neurotropismmentioning
confidence: 99%
“…In addition to the astroglial role in preventing CNS spreading of MHV-A59, microglia seem also to be required to control neurotropic CoV infection. A recently published article showed that depletion of microglia using PLX5622, an inhibitor of colony-stimulating factor 1 receptor (CSF1R), in animals exposed to JHM-MHV increased mortality, impaired control of viral replication, altered CD4+ and CD8+ T-cell infiltration, increased demyelination, and decreased neuro-repair ( Mangale et al., 2020 ).…”
Section: Animal Cov That Show Neurotropismmentioning
confidence: 99%
“…2 ). On one hand, microglial cells act in the innate immune response in the CNS and are essential for restricting viral replication and activating proper systemic anti-viral responses ( Wheeler et al., 2018 ; Klein et al., 2019 ; Mangale et al., 2020 ). On the other hand, these cells can also have detrimental effects, indirectly by activating astrocyte-mediated neurotoxicity ( Tremblay et al., 2011 ) and directly by inducing synapse loss ( Klein et al., 2019 ; Trzeciak et al., 2019 ) ( Fig.…”
Section: Glial Cells Covs and Other Neurotropic Virusesmentioning
confidence: 99%
“…For example, in an in vivo murine model of infection with the neurotropic JHM strain of mouse hepatitis virus (JHMV), microglial cells are necessary for effective restriction of viral replication in the CNS. Furthermore, microglial depletion disturbs the host systemic T cell anti-viral response and leads to increased neurological manifestations (demyelination), morbidity and mortality ( Wheeler et al., 2018 ; Mangale et al., 2020 ).…”
Section: Glial Cells Covs and Other Neurotropic Virusesmentioning
confidence: 99%
See 2 more Smart Citations